Wage growth and labor market tightness - Sebastian Heise; Jeremy Pearce; Jacob P. Weber (Federal Reserve Bank of New York, 2024)
Good measures of labor market tightness are essential to predict wage inflation and to calibrate monetary policy. This paper highlights the importance of two measures of labor market tightness in determining wage growth: the quits rate and vacancies per effective searcher (V/ES)-where searchers include both employed and non-employed job seekers. Amongst a broad set of indicators of labor market tightness, we find that these two measures are independently the most strongly correlated with wage inflation and also predict wage growth well in out-of-sample forecasting exercises. Conversely, transitory shocks to productivity have little impact on wage growth. Finally, we find little evidence of a nonlinearity in the relationship between wage growth and labor market tightness. These results are generally consistent with the predictions of a New Keynesian DSGE model where firms have the power to set wages and workers search on the job (Bloesch, Lee, and Weber, 2024).
Keywords: E3; J6; 330; wage Phillips curve; labor market slack; labor market tightness; on-the-job search